On effectiveness of cooperation enforcement mechanisms in wireless ad hoc networks. (1st January 2012) - Chaturvedi, Manish; Srivastava, Sanjay
Wireless ad hoc networks are resource constrained, infrastructureless peer to peer networks where nodes are responsible for performing routing activity for other nodes to establish end to end communication. Due to limited resources (energy and bandwidth), in certain networks, nodes may behave selfishly and not forward packets for other nodes. Many cooperation enforcement mechanisms are proposed in literature to enforce packet forwarding on resource constrained nodes, and are shown to perform better than the defenseless dynamic source routing (DSR) protocol under their own set of assumptions. However, they do not consider the effect on network lifetime and energy consumption. Here we analyse routing overhead, end to end packet delivery ratio (PDR), and per packet energy cost of DSR and a representative set of cooperation enforcement mechanisms using various network scenario to show that in absence of infrastructure support cooperation enforcement mechanisms in their present form are not effective in dealing with node selfishness.